Rumah Persulukan Tuan Guru Musa: Studi Tentang Interaksi Agama di Kabupaten Labuhanbatu Utara - Susilawati; Rholand Muary (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Rumah Persulukan Tuan Guru Musa serves as a central hub for religious and cultural learning, playing a crucial role in shaping the local community's culture. Within this "persulukan" environment, the developing culture is heavily influenced by learning, ethics, traditions, and local customs. This research utilized a descriptive qualitative method to investigate the development of Rumah Suluk Tuan Guru Musa, from its history to its current activities. The findings of this study outline the history of the leadership of Rumah Persulukan and the various activities carried out, such as worship, spiritual practices, and cultural traditions, all of which demonstrate a close blend of religious teachings and local customs, strongly supported by both the community and the government. Based on the analysis, Rumah Persulukan Tuan Guru Musa functions as an important center for religious and cultural learning, significantly influencing the local community's culture.